2002
DOI: 10.1034/j.1600-0447.2002.02346.x
|View full text |Cite
|
Sign up to set email alerts
|

Living situation, subjective quality of life and social network among individuals with schizophrenia living in community settings

Abstract: People with schizophrenia with an independent housing situation have a better quality of life associated with more favorable perceptions of independence, influence, and privacy. Their social network is better irrespective of whether they live alone or not, or with family or not.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
64
1
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(73 citation statements)
references
References 23 publications
6
64
1
2
Order By: Relevance
“…For men, who constituted the majority of participants in our study, we concluded, in accordance with earlier studies (Hansson et al, 2002, Wheeler, 2007, that most of them lived alone, were neither married nor in a close relationship, had no daily occupation, and experienced a more unsatisfactory quality of life. The study also showed that people with SMI and psychiatric functional disabilities living in a community may require not only psychiatric care, but somatic, dental, and social services as well.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…For men, who constituted the majority of participants in our study, we concluded, in accordance with earlier studies (Hansson et al, 2002, Wheeler, 2007, that most of them lived alone, were neither married nor in a close relationship, had no daily occupation, and experienced a more unsatisfactory quality of life. The study also showed that people with SMI and psychiatric functional disabilities living in a community may require not only psychiatric care, but somatic, dental, and social services as well.…”
Section: Discussionsupporting
confidence: 91%
“…Indications of this comes from research documenting increased criminality, drug abuse, suicide, higher mortality, homelessness, isolation, lack of meaningful occupations and underutilization of social care and support systems in this population (Belfrage, 1994;Appleby, 1992;Wahlbeck et al, 2011;Scott, 1993: Beebe, 2010Evert et al, 2003, Hansson et al, 2002.…”
Section: Introductionmentioning
confidence: 99%
“…210 Studies that directly compare mental illness and general population networks also show smaller networks for people with mental illness. 45,109 Therefore, compared with the general population, the connections within this group were likely to be less 'diverse and active'.…”
Section: Data Limitationsmentioning
confidence: 99%
“…Furthermore, housing is an important determinant of mental health for people with intellectual disabilities (McGlaughlin 2004). A number of studies have addressed the outcome of different types of housing for people with psychiatric disabilities (Hansson et al 2002;Kyle and Dunn 2008;Nelson et al 1998;Oliver and Mohamad 1992) and intellectual disabilities (Emerson 2004;McConkey 2007;Perry and Felce 2003;Young 2006). Studies indicate limitations in community-based housing opportunities for people with psychiatric disabilities and conclude that homelessness is all too commonly experienced by people discharged from hospital wards (Burt et al 2007;Forchuk et al 2006;Kuno et al 2000;Nordentoft et al 1997).…”
Section: Introductionmentioning
confidence: 99%